ANALYSIS OF SPATIAL DISTRIBUTION OF HEALTHCARE FACILITIES USING GEOGRAPHIC INFORMATION SYSTEM, JEMA’A LOCAL GOVERNMENT AREA, KADUNA STATE (FUDMA JOURNAL OF SCIENCES, 2020)
Healthcare facilities form integral component of healthcare system. It is centers where preventive and curative services are provided and allow referral from simple to complex service provision. Access to healthcare is multi-dimensional but one can narrow it to geographical availability. Jema’a LGA is faced with serious problem healthcare facilities provision and this is not disconnected with continuous increase in population and expansion communities without corresponding investment in healthcare sector by key actors. This has resulted in congestion and overstretching of existing healthcare facilities, making accessibility difficult. However, with recent behavior of patients toward some healthcare facilities, the study aimed at analyzing the distribution of healthcare facilities in Jema’a LGA using Geographic Information System. To achieve this, Geographic coordinates of healthcare facilities were acquired by hand held Garmin ETREX. Total sampling techniques was employed and questionnaire was administered to generate information for healthcare facilities. Data generated was used to create a database. The results revealed 55(100%) healthcare facilities in all; 30(54.5%) healthcare facilities were governments owned and 25(45.5%) private. Further query revealed 53 healthcare facilities were primary and 1 was secondary type. Only 2 out of 54 healthcare facilities were equipped and are discharging good healthcare services. Spatial auto-correlation was used to establish the pattern of distribution. The distribution pattern of healthcare facilities does not appear significantly different other than random. The study recommends all issues regarding healthcare facilities such as upgrade; equipping and new provision of healthcare facilities should be giving emergency attention by all stakeholders.
Keywords: Database, mapping, spatial distribution, healthcare facilities, geographic coordinates